GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 3135 species occurrences available in GBIF matching the query: TaxonKey: Urocitellus columbianus (Ord, 1815). The dataset includes 3135 records from 52 constituent datasets: 3 records from SUI Vertebrate Collection. 11 records from ISM Mammalogy Collection. 1 records from CSUC Vertebrate Collection. 99 records from MVZ Mammal Collection (Arctos). 352 records from KUBI Mammalogy Collection. 13 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 5 records from CUMV Mammal Collection (Arctos). 8 records from UAM Mammal Collection (Arctos). 1 records from The mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 541 records from CRCM Vertebrate Collection. 68 records from Cowan Tetrapod Collection - Mammals. 1 records from HSU Wildlife Mammals. 32 records from Field Museum of Natural History (Zoology) Mammal Collection. 1 records from CHAS Mammalogy Collection (Arctos). 3 records from Naturalis Biodiversity Center (NL) - Mammalia. 52 records from iNaturalist Research-grade Observations. 1 records from Mammal collection, Natural History Museum, University of Oslo. 11 records from naturgucker. 60 records from CAS Mammalogy (MAM). 551 records from UMMZ Mammal Collection. 2 records from Mammal Collection. 1 records from SBMNH Vertebrate Zoology. 5 records from LACM Vertebrate Collection. 19 records from Macaulay Library Audio and Video Collection. 163 records from NatureServe Network Species Occurrence Data. 1 records from ISU Mammals. 310 records from NMNH Extant Specimen and Observation Records. 122 records from UWBM Mammalogy Collection. 7 records from Mammal specimens. 1 records from LSUMZ Mammals Collection. 2 records from Mammals Specimens. 7 records from FHSM Mammals Collection. 3 records from CNMA/Colección Nacional de mamíferos. 35 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 24 records from TTU Mammals Collection. 10 records from UCLA Donald R. Dickey Bird and Mammal Collection. 3 records from WNMU Mammal Collection (Arctos). 189 records from University of Alberta Museum of Zoology Mammalogy Collection (UAMZ). 5 records from UCM Mammal Collection (Arctos). 53 records from PSM Vertebrates Collection. 3 records from MCNH Museum of Cultural and Natural History Mammals Collection. 9 records from UAZ Mammals. 2 records from Collection Mammalia SMF. 158 records from AMNH Mammal Collections. 1 records from Queensland Museum provider for OZCAM. 5 records from Geographically tagged INSDC sequences. 48 records from MSB Mammal Collection (Arctos). 48 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 79 records from Mammalogy Collection - Royal Ontario Museum. 1 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 2 records from UWYMV Mammal Collection (Arctos). 3 records from Angelo State Natural History Collections (ASNHC) - Mammalogy Collection. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences